2022
DOI: 10.1136/bjsports-2021-104755
|View full text |Cite
|
Sign up to set email alerts
|

Pushing for change: a qualitative study of the experiences of elite athletes during pregnancy

Abstract: ObjectivesAthletes train and compete at the elite level during their reproductive years, yet sport policies that support pregnant athletes are lacking. The experiences of elite athletes during pregnancy are vastly under-represented, and such voices are needed to support evidence-informed policy. Thus, the purpose of this qualitative study was to describe the experiences of elite female athletes as they navigate pregnancy, and to identify sport policy considerations regarding participation during pregnancy.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 20 publications
3
37
0
Order By: Relevance
“…For instance, qualitative research with competitive recreational athlete mothers described the various cultural (e.g., the cultural norm that a “good” mother prioritizes her child over herself), personal (e.g., attempting to balance motherhood, work and sport with a limited amount of time), and social (e.g., childcare, emotional support to engage in sport) barriers that impact sport participation [ 11 ]. Similar findings have been noted in research that has documented the in-depth experiences of elite athletes who returned to elite-level sport following childbirth [ 1 , 3 , 12 16 ]. In their research with elite distance runners, Appleby and Fisher [ 14 ] described how athletes who returned to competition after pregnancy experienced a transformative process in which they negotiated social stereotypes related to motherhood alongside their athletic identities [ 14 ].…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…For instance, qualitative research with competitive recreational athlete mothers described the various cultural (e.g., the cultural norm that a “good” mother prioritizes her child over herself), personal (e.g., attempting to balance motherhood, work and sport with a limited amount of time), and social (e.g., childcare, emotional support to engage in sport) barriers that impact sport participation [ 11 ]. Similar findings have been noted in research that has documented the in-depth experiences of elite athletes who returned to elite-level sport following childbirth [ 1 , 3 , 12 16 ]. In their research with elite distance runners, Appleby and Fisher [ 14 ] described how athletes who returned to competition after pregnancy experienced a transformative process in which they negotiated social stereotypes related to motherhood alongside their athletic identities [ 14 ].…”
Section: Introductionsupporting
confidence: 84%
“…We and others have previously described that many athletes worry that their decision to become a mother can permanently derail their athletic career [ 1 , 4 ]. Indeed, our athletes described a wide variety of experiences from personal best performances, to months and years plagued by injury and stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of a supportive organisational culture, women athletes report worry about disclosing pregnancy due to fear of being viewed as not dedicated to their sport, and therefore, delay disclosing this information until late in pregnancy. In contrast, this work reported that organisations with clear policies and regulations about the financial support for women athletes including eligibility requirements enabled athletes to make informed family planning decisions 50…”
Section: Resultsmentioning
confidence: 77%